AN ANALYSIS OF STUDENTS’ ANXIETY IN SPEAKING ENGLISH AT MAN I KOLAKA - Rohima Nur Aziza Al Hakim; Hariadi Syam (Universitas Negeri Makassar, 2019)
ABSTRACTThis research was aimed to investigate; (1) the factors of students’ anxiety in speaking English; and (2) the strategies used by the students in overcoming their anxiety in speaking English at the first grade of MAN I Kolaka. This research used a mix method namely quantitative and qualitative. In conducting the research, the researcher collected the data by using questionnaire and interview. The participant of this research were 30 students of class X IPA 1. The result of this research showed that the factors of students’ anxiety in speaking English of MAN 1 Kolaka were communicative apprehension, with mean value (3,82) test anxiety with mean value (3,4) fear of negative evaluation with mean value ( 3,67). The result of interviewed showed that there were five strategies that students used to overcome their anxiety in speaking English such as: preparation, relaxation, positive thinking, peer seeking and resignation.